Studi Analisis Metode Bina Pribadi Islam (BPI) Untuk Meningkatkan Rasa Empati Peserta Didik Sekolah Dasar (SD) Islam Al-Hikmah Sempor - Savitri, Yanuariva Agiel; Eliyanto, Eliyanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The research objectives are: (1) Analyze the implementation of the Bina Pribadi Islam (BPI) method in Al-Hikmah Islamic Elementary School Sempor in contributing to the peningkatan rasa empati (enhancement of empathy) of students; (2) To identify the supporting and inhibiting factors in influencing the Bina Pribadi Islam (BPI) method on the peningkatan rasa empati (enhancement of empathy) of students. This research is a qualitative study. The respondents in this study are students of grade IV, BPI Instructor Teachers, and the Principal of Al-Hikmah Islamic Elementary School Sempor. The research method used is qualitative with a field research approach. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the Bina Pribadi Islam (BPI) method is effective in enhancing the peningkatan rasa empati (enhancement of empathy) of students of Al-Hikmah Islamic Elementary School Sempor. This is evidenced by the development of the Attitude of Empathy (attitude of empathy) of students in Classes IV A and IV B of Al-Hikmah Islamic Elementary School in the 2023/2024 academic year, which has shown a significant improvement.